Dua Dekade Kebebasan Akademik di Indonesia: Tantangan di Tengah Menguatnya Otoritarianisme dalam Model Barunya - Herlambang Perdana Wiratraman; Satria Unggul Wicaksana Prakasa (Badan Strategi Kebijakan Hukum, 2024)
This research focuses on analyzing the debates and roles of the academic freedom movement in Indonesia's authoritarian politics. Numbers of scholars argued on the democracy decline and its current situation of authoritarian turn (Mietzner 2016, 2020; Hadiz 2017; Wiratraman 2018; Waburton and Aspinal 2019; and Winters 2021). Authoritarianism governance in recent politics has been worsening situation of free expression, including academic freedom. Recently, one of attacks is connected to cyber-attacks, which has been targeting journalists, academics, activists or students who defend human rights and environment, indigenous leaders, anti-corruption activists, and women's groups. This article discusses first, how has academic freedom at campuses been shaped by Indonesia's the rise of authoritarian politics; and second how academic freedom has been influenced and easily attacked in the rise of digital authoritarianism. By using an interdisciplinary approach, this article argues that there is a strong relation between the threat of academic freedom and the strengthening of authoritarianism in Indonesia, especially by disciplining campuses through a more systematic bureaucratization. While at the same time, academic freedom has been affected by stronger control of authoritarianism regime by deplying cyber troops in digital spheres. Hence, this article also discusses how human rights instruments and its institutions could promote and defend academic freedom in general.